Who jumps the highest? Measuring gazelle companies’ high-growth performance using a PSM and MABAC - Pestana, C.; Ferreira, F.; Teixeira, F.; Ferreira, J.; Ferreira, N. (EuroMed Journal of Business)
Purpose: This study aims to develop a multicriteria decision analysis (MCDA) evaluation system to assess the high-growth performance of gazelle companies. It seeks to support a better understanding of the factors that drive rapid business expansion and to contribute to debates on how to effectively define and measure high-growth firms. Design/methodology/approach: A constructivist approach is adopted, combining cognitive mapping and the Multi-Attributive Border Approximation area Comparison (MABAC) method. A panel of decision makers with practical experience in gazelle companies participated in two working sessions to structure the evaluation framework and assess performance. A separate consolidation session was held with two representatives from the Committee for Central Region Coordination and Development (i.e., Comissão de Coordenação e Desenvolvimento Regional do Centro—a public entity that grants gazelle awards in Portugal). Findings: The study produces a tailored MCDA evaluation system that enables the structured evaluation of gazelle companies’ growth trajectories, highlighting key determinants of rapid expansion. It also demonstrates the value of incorporating expert knowledge and stakeholder validation in assessing firm performance in complex, data-scarce contexts. Originality: This study contributes to the literature by combining a problem structuring method (PSM) (i.e., cognitive mapping) and MABAC to evaluate gazelle companies—an area where consistent measurement frameworks are lacking. It also provides a novel application of these methods in collaboration with a regional development authority, reinforcing the system’s practical relevance and usability.